Física e o som: possibilidades didáticas e experimentais para o ensio de acústica - Ceschi, Wander Henrique Gomes [UNESP] (Universidade Estadual Paulista (Unesp), 2015)
We studied in this work some aspects of the physics of sound and music as a tool for physics teaching. The theory of sound since it is generated by some stimulus to its uptake by the human body, in areas such as: frequency, intensity, tone and propagation. The literature of the subject research was combined with the study of free software that captures waves on a computer, using a microphone, and allows to analyze the waves and frequencies involved in the sound, being able to distinguish tones, frequencies and intensities. We have analyzed some instruments (guitar, harmonica and pitch), including voice, from the quantitative and qualitative point of view. Finally we analyze textbooks in their acoustic topics and try to understand how important these materials give to this topic in basic education. We suggest a teaching sequence that could be applied in a high school classroom

Estudamos neste trabalho alguns aspectos da física dos sons e da música como ferramenta para o ensino de física. A teoria trata do som desde que é gerado por algum estimulo até sua captação pelo corpo humano, em aspectos como: Frequência, intensidade, timbre e propagação. A pesquisa bibliográfica do assunto foi aliada ao estudo de um software gratuito que capta ondas em um computador, utilizando um microfone, permite analisar as ondas e frequências envolvidas no som, podendo-se assim distinguir timbres, frequências e intensidades. Analisamos alguns instrumentos (violão, gaita e diapasão), inclusive a voz, sob o ponto de vista qualitativo e quantitativo. Por fim analisamos livros didáticos em seus tópicos de acústica e procuramos entender qual a importância que esses materiais dão à esse tópico no ensino básico. Sugerimos uma sequência de ensino que poderia ser aplicada numa sala de aula de Ensino Médio
Keywords: Acustica; Física - Estudo e ensino; Musica - Acustica e fisica; Som; Instrumentos musicais